Power, Royalty, Style: the Strange Case of Henry VII and Perkin Warbeck - Roberto D'Avascio (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2024)
This essay offers a close reading of John Ford’s Perkin Warbeck (“a history play about the end of history plays”, Taylor 2008) which re-proposes the (hi)story of a pretender to the throne, who challenges the legitimacy of Henry VII in a fully Stuart era. The essay considers issues of dramaturgy and historiography/history on stage, against the backdrop of the passage of the English throne from Elizabeth I to James I, which marked an epochal dynastic transition in English history and an overall change in the cultural climate that particularly affected the theatre.